2021
DOI: 10.1123/jcsp.2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

What Lies Beneath: Exploring Different Depressive Symptoms Across Selected Risk Factors in Icelandic Team Sport Athletes

Abstract: The aim of the study was to explore the prevalence of specific symptoms of depression in athletes and to test differences in the likelihood of athletes exhibiting these symptoms across age, sex, type of team sport, and level of competition. A sample of Icelandic male and female team sport athletes (N = 894, 18–42 years) was included in the study. Of the athletes exhibiting clinically significant depressive symptoms on the Patient Health Questionnaire-9, 37.5% did not exhibit core symptoms of depression. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(138 reference statements)
1
2
0
Order By: Relevance
“…Sex differences are observed in the prevalence of depression at both the general population and athlete level [ 26 ], with females being more likely to report depressive symptoms than males. Our findings were consistent with existing research in other sports [ 4 , 27 ], whereby the prevalence of depression in WAFL-W players (57.1%) was almost three times greater than in WAFL-M (19.8%) players, with one study of Australian elite soccer players and another in Icelandic athletes (football, handball and basketball) indicating women were almost twice as likely to experience moderate to severe depression symptoms than men [ 4 , 27 ]. It is important to note that these findings need to be interpreted with caution due to the low number of women within our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Sex differences are observed in the prevalence of depression at both the general population and athlete level [ 26 ], with females being more likely to report depressive symptoms than males. Our findings were consistent with existing research in other sports [ 4 , 27 ], whereby the prevalence of depression in WAFL-W players (57.1%) was almost three times greater than in WAFL-M (19.8%) players, with one study of Australian elite soccer players and another in Icelandic athletes (football, handball and basketball) indicating women were almost twice as likely to experience moderate to severe depression symptoms than men [ 4 , 27 ]. It is important to note that these findings need to be interpreted with caution due to the low number of women within our study.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of depression symptoms in our WAFL-W players was also substantially higher (57.1%) than Australian women with diagnosed affective disorders (16–24 years = 19.0%) [ 2 ], a previous study of Australian elite women’s soccer players (10.6%) [ 4 ] and Icelandic women athletes (12.2%) [ 27 ]. However, as with other areas of sports and exercise medicine, women remain substantially under-represented in research [ 10 ].…”
Section: Discussionmentioning
confidence: 74%
“…Male first league players had significantly lower average depression scores than male U-21 and female players; whereas, other studies found that younger athletes had lower stress levels and higher well-being than older athletes (e.g., Belz et al, 2018). A study with Icelandic team-sport athletes suggested that although female athletes may be more likely than males to experience moderate levels of depressive symptoms, the rates of more severe symptomology may be comparable between the sexes (Tahtinen, Kristjansdottir, Olason, & Morris, 2021). Prinz, Dvorak, and Junge (2016) found that average depression scores differed significantly between playing positions and levels of play in the German league, and conflicts with management contributed additionally to higher scores.…”
mentioning
confidence: 87%